Building the Basics of Gender Mainstreaming in Strengthening the Legal System in Indonesia - Ni Putu Yuliana Kemalasari; I Nengah Pasek Suryawan (Journal Equity of Law and Governance, 2025)
The World Conference on Women held in Nairobi in 1985 has greatly changed the gender paradigm throughout the world. It was at this conference that the term gender mainstreaming was first introduced. Gender issues are problems that always have pros and cons in a social system in society, which then has an impact on the legal system in a country. A country becomes strong if it is supported by a strong legal system. Therefore, building the foundations for gender mainstreaming in strengthening the legal system will be a strategic step to create a legal system that is inclusive and fair for all parties, especially marginalized parties. The research method used to examine problems related to how to build the foundations of gender mainstreaming in the legal system is the normative juridical method. Gender mainstreaming in the legal system includes the integration of gender perspectives in every process of creating, implementing, and evaluating legal policies. In order to strengthen the legal system, gender mainstreaming also involves drafting more gender-sensitive regulations with effective monitoring mechanisms to avoid discriminatory acts.